Investigating freedom to learn program as a form of education decentralization in Indonesia - Senatama, Gandung; Tri Kartono, Drajat (Ittishal Educational Research Journal, 2023)
Education is one of Indonesia's goals as stated in the fourth paragraph of the 1945 Constitution. However, the decentralization problem of education through transformational schools found various obstacles. This study aims to explore the problems of decentralization of education of the Freedom to Learn program through transformational schools spread throughout Indonesia. This study used the literature study method obtained from literature and books and with VOSViewer software which analysed 2.339 social articles discussing decentralization. The results of the research showed that decentralization implementation of education through transformational schools met obstacles such as inadequate facilities and many teachers are struggling to use technology, so the decentralization process is not maximal. The researchers suggest that the government should provide space for policy targets from lower levels spread throughout Indonesia so that the education decentralization process can run.